(untitled) (American Journal of Islam and Society, 2023)
Continuing engagement with Islamic legal scholarship does not seem to have resulted in satisfactory attention being paid to the interplay of philosophical considerations and theological principles in relation to the ethical component of Islamic Law. This explains why any scholarly and properly guided attempt to extend the frontiers of knowledge on the subject of Islamic Law and Ethics is always welcome. David Vishanoff’s edited volume examines Islamic ethics in the context of Islamic law. The book comprises an introduction by the editor, a foreword by the publishers, followed by the chapters contributed by the editor and no fewer than six other eminent scholars on various aspects of the subject, which are presented in an elegant, lucid, and highly intelligible prose. The editor’s introduction, Islamic Law and Ethics: From Integration to Pluralism (pp. ix-xiii) provides the rationale for the book, exposes the gap that the book seeks to fill, and offers a panoramic picture of the central theme as addressed by the various contributors in their respective chapters.